Can compression garments reduce the deleterious effects of physical exercise on muscle strength? a systematic review and meta-analyses - Négyesi, J.; Hortobágyi, T.; Hill, J.; Granacher, U.; Nagatomi, R. (Sports Medicine, 2022)
Background: The use of compression garments (CGs) during or after training and competition has gained popularity in the last few decades. However, the data concerning CGs` beneficial effects on muscle strength-related outcomes after physical exercise remain inconclusive. Objective: The aim was to determine whether wearing CGs during or after physical exercise would facilitate the recovery of muscle strength-related outcomes. Methods: A systematic literature search was conducted across five databases (PubMed, SPORTDiscus, Web of Science, Scopus, and EBSCOhost). Data from 19 randomized controlled trials (RCTs) including 350 healthy participants were extracted and meta-analytically computed. Weighted between-study standardized mean differences (SMDs) with respect to their standard errors (SEs) were aggregated and corrected for sample size to compute overall SMDs. The type of physical exercise, the body area and timing of CG application, and the time interval between the end of the exercise and subsequent testing were assessed. Results: CGs produced no strength-sparing effects (SMD [95% confidence interval]) at the following time points (t) after physical exercise: immediately = t < 24 h: - 0.02 (- 0.22 to 0.19), p = 0.87; 24 = t < 48 h: - 0.00 (- 0.22 to 0.21), p = 0.98; 48 = t < 72 h: - 0.03 (- 0.43 to 0.37), p = 0.87; 72 = t < 96 h: 0.14 (- 0.21 to 0.49), p = 0.43; 96 h = t: 0.26 (- 0.33 to 0.85), p = 0.38. The body area where the CG was applied had no strength-sparing effects. CGs revealed weak strength-sparing effects after plyometric exercise. Conclusion: Meta-analytical evidence suggests that wearing a CG during or after training does not seem to facilitate the recovery of muscle strength following physical exercise. Practitioners, athletes, coaches, and trainers should reconsider the use of CG as a tool to reduce the effects of physical exercise on muscle strength.